Evidence brief: Creating resilient and responsive mental health systems for children, youth and families during and beyond the COVID-19 pandemic in Ontario - Gauvin, François-Pierre; Moat, KA; Bain, T; Lavis, JN (My University, 2021)
An assessment of what is known about problems related to mental health systems during and beyond the COVID-19 pandemic, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of creating resilient and responsive mental health systems for children, youth and families during and beyond the COVID-19 pandemic in Ontario.
Keywords: resilient; responsive; mental health systems; children; youth; families; COVID-19; Ontario